Factors Associated with Recurrence in Chronic Subdural Hematoma following Surgery - Buakate, Kritsada; Tunthanathip, Thara (Journal of Health and Allied Sciences NU, 2023)
Background Recurrence is a frequent complication after surgery in a chronic subdural hematoma (CSDH). This study aimed to describe the recurrent rate of CSDH after surgery. In addition, a secondary objective aimed to explore factors associated with the recurrence of CSDH after surgery.Methods A total of 141 surgical CSDH patients were analyzed in this retrospective study. The Cox regression method was used to conduct both univariate and multivariate analyses of variables associated with recurrence. As a result, the cumulative incidence of recurrence for each covariate survival curve was built after the final model.Results Twenty-two percent of the patients showed evidence of recurrence. Initially, four variables (Glasgow coma scale score 3–8, clopidogrel, operative time, and amount of irrigated saline) had potential factors in univariate analysis but only clopidogrel and amount of saline irrigation were significantly associated with CSDH recurrence.Conclusion Preoperative clopidogrel and the amount of saline irrigation were found to be associated with the recurrence rate. Factors associated with CSDH recurrence should be developed and validated as the clinical prediction tool for implication in general practice.
Keywords: Chronic Subdural Hematoma; burr hole; recurrence; traumatic brain injury